Pengaruh edukasi gizi terhadap pengetahuan gizi atlet remaja di Indonesia - Penggalih, Mirza Hapsari Sakti Titis; Sofro, Zaenal Mutaqqien; Trisnantoro, Laksono; Susila, Edi Nurinda; Ernawaty, Ernawaty; Rahadian, Bayu; Margono, Margono; Sujadi, Dadi; Isnanta, Raden; Bactiar, Nia; Anugraheni, Ayudiva Rizky; Budiarjo, Theresa (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2023)
The impact of providing nutrition education on the nutritional knowledge of young athletes in IndonesiaBackground: A lack of nutritional knowledge can lead to poor eating habits and nutritional deficiencies in young athletes. One of the issues leading to athletes' need for more knowledge is the absence of professional assistance in educating them about nutrition. Objective: This research was analyzed to investigate the impact of nutrition education through counseling and group-based nutrition education on the nutritional knowledge of young athletes in Indonesia. Methods: This study is a pre-and post-experimental study without control. One hundred eighty-five young athletes who trained in PPLP and SKO received nutrition intervention for two months, including three nutrition education sessions using sports nutrition module media, nutritional counseling, and eating assistance based on eating etiquette. A modified Abridged Nutrition for Sport Knowledge Questionnaire (ANSKQ) questionnaire assessed athletes' nutritional knowledge before and after the intervention. Data was examined by comparing scores before and after the intervention. The Kolmogorov-Smirnov test was used in the normality test, and a paired t-test was used to compare nutritional knowledge before and after the intervention. Results: Before the intervention, 88.65% had a low level of knowledge about nutrition. The scores for sports nutrition and overall nutritional knowledge increased significantly (p<0.05). The scores of general nutrition knowledge increased but were not significant (p>0.05). Conclusions: There was a significant increase in sports nutrition knowledge but not general nutrition knowledge. The provision of nutritional education assisted by nutritionists impacts athletes' nutritional knowledge.